1991
DOI: 10.1080/02678299108028228
|View full text |Cite
|
Sign up to set email alerts
|

Comparing X-ray studies of smectic A phases formed by laterally branched molecules

Abstract: By observation of optical and miscibility studies the liquid-crystalline phases of compounds with the general formula 0 C H II l 7 l5 Notation-code: nR, have been classified. The structures of the S, phases of the pure compounds as well as of mixtures with rod-like molecules have been studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 10 publications
(4 reference statements)
1
8
0
Order By: Relevance
“…Baumeister, et al (1990) synthesized a compound 4-ethoxy-2′-(4-ethoxyphenyliminomethyl)-4'-(4-methoxybenzoyloxy) azobenzene with the observation of the nematic (N) phase. Same feature was observed in the study done by Diele, et al, 1991, where the N and S m A phases were been observed. Berdague, et al (1993) reported new laterally aromatic branched liquid crystal (LC) materials with the N and S m C phases.…”
Section: Introductionsupporting
confidence: 67%
“…Baumeister, et al (1990) synthesized a compound 4-ethoxy-2′-(4-ethoxyphenyliminomethyl)-4'-(4-methoxybenzoyloxy) azobenzene with the observation of the nematic (N) phase. Same feature was observed in the study done by Diele, et al, 1991, where the N and S m A phases were been observed. Berdague, et al (1993) reported new laterally aromatic branched liquid crystal (LC) materials with the N and S m C phases.…”
Section: Introductionsupporting
confidence: 67%
“…Gray [21] has proposed that this rarity is associated with intermolecular hydrogen bonding raising the melting point above the mesophase-isotropic liquid transition temperature, and perhaps also encouraging a nonlinear molecular arrangement that is incompatible with mesophase formation. After an initial investigation by Weissflog and Demus [22], a number of homologues series with a trisubstituted benzene nucleus have been reported [23][24][25][26][27][28][29][30]. Schroeder and Schroeder [31] reported a few terminally hydroxy substituted mesogens.…”
Section: Introductionmentioning
confidence: 99%
“…This parallel arrangement seems to be connected with the sterically induced destabilization of the mesophase found by Jacobi et al 13) For our samples, the more stable phases are connected with a perpendicular arrangement; a parallel structure means a destabilization! Additionally, the wedge-like shape of these mesogens 22) must be taken into account for further discussions.…”
Section: Discussionmentioning
confidence: 99%